2006
DOI: 10.1523/jneurosci.0023-06.2006
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatitis-Associated Protein-III Is a Novel Macrophage Chemoattractant Implicated in Nerve Regeneration

Abstract: Circulating macrophages are recruited to degenerating nerves in response to nerve injury to remove myelin and axonal debris, a process that is crucial for successful nerve regeneration. In this study, we demonstrate that pancreatitis-associated protein (PAP)-III is a macrophage chemoattractant that is induced in and released from injured nerves. In vitro experiments revealed that PAP-III possessed a strong macrophage chemoattractant activity that was comparable with that of monocyte chemoattractant protein-1. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
49
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(51 citation statements)
references
References 45 publications
1
49
1
Order By: Relevance
“…Expression of PAP I and PAP II is strongly induced in dorsal root ganglion (DRG) neurons following peripheral tissue inflammation and nerve injury suggesting an important role in the modulation of spinal sensory pathways in chronic pain states (He et al 2010). PAP III appears to have a specific role in peripheral nerve regeneration (Namikawa et al 2005(Namikawa et al , 2006. Very recent reports from rat models of brain injury, particularly, in neuroinflammation associated with TBI (Ampo et al 2009) as well as in kainic acid-induced brain seizure (Kawahara et al 2011) demonstrate elevated PAP I and PAP III expression also in central neurons.…”
Section: Introductionmentioning
confidence: 99%
“…Expression of PAP I and PAP II is strongly induced in dorsal root ganglion (DRG) neurons following peripheral tissue inflammation and nerve injury suggesting an important role in the modulation of spinal sensory pathways in chronic pain states (He et al 2010). PAP III appears to have a specific role in peripheral nerve regeneration (Namikawa et al 2005(Namikawa et al , 2006. Very recent reports from rat models of brain injury, particularly, in neuroinflammation associated with TBI (Ampo et al 2009) as well as in kainic acid-induced brain seizure (Kawahara et al 2011) demonstrate elevated PAP I and PAP III expression also in central neurons.…”
Section: Introductionmentioning
confidence: 99%
“…In vitro studies showed that PAP expression is also upregulated by free radicals or cytokines, and such upregulation confers cellular resistance to apoptosis (6). Recent studies have shown that PAP III can serve as a macrophage chemoattractant during inflammation and is involved in peripheral nerve regeneration (7).…”
Section: Introductionmentioning
confidence: 99%
“…PAP1 has been shown to inhibit macrophage activation by down-regulating the synthesis of TNF-␣ and IL-6, thereby promoting an anti-inflammatory state (15). PAP3 has been shown to be a macrophage chemokine, recruiting macrophages to areas of neuronal damage (18). Here, we demonstrate that PAP2 mediates the up-regulation of inflammatory cytokines and stimulates macrophage activity thus identifying a new function for PAP2: it is a modulator of the inflammatory response.…”
Section: Discussionmentioning
confidence: 63%
“…Although some have shown that PAP1 protects against the lung injury during pancreatitis (16), others have shown that high doses of PAP1 can induce lung inflammation (17). PAP3 has been shown to be a strong macrophage chemokine (18), and the mouse homolog to PAP3 (referred to as Reg3␥) has been shown to be involved in innate immunity (19). We have demonstrated that various Reg/PAP isoforms appear to increase in pancreatitis (20,21), suggesting an immunomodulatory relationship within the Reg family.…”
mentioning
confidence: 75%